Growth, production and reproduction performance of tellicherry goats under intensive and semi-Intensive systems of management - K. Chinnamani; V. Ramesh Saravana Kumar; J. Muralidharan; A.K.Thiruvenkadan; S. SureshKumar; P.Vasantha Kumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was undertaken on the growth, productive and reproductive performance of Tellicherry goats under intensive and semi-intensive systems of management using 40 kids. The overall body weights at birth, 3, 6, 9 and 12 months of age under intensive system were 2.33 ± 0.10, 9.51 ± 0.33, 14.10 ± 0.53, 19.16 ± 0.75 and 20.13 ± 0.83 Kg, respectively. Similarly, under semi-intensive system the values were 1.96 ± 0.05, 7.65 ± 0.11, 14.15 ± 0.52, 18.46 ± 0.64 and 20.48 ± 0.46 Kg, respectively. Under intensive system, the reproductive performance namely weight at first mating, number of services per conception, weight at first kidding, litter size, gestational weight gain, lactational weight loss, service period, kidding percentage and kidding interval were 18.51 ± 0.86 kg, 1.25 ± 0.13, 22.87 ± 0.75 kg, 1.08 ± 0.08, 4.36 ± 0.33kg, 3.28 ± 0.43kg, 89.00 ± 1.85 days, 100.00, 245.01 ± 3.84 days, respectively. The same values for semi-intensive system were 18.13 ± 0.87 kg, 1.50 ± 0.23, 23.35 ± 0.98kg, 1.25 ± 0.13, 5.22 ± 0.50kg, 2.92 ± 0.72, 85.30 ± 2.12 days, 100.00, 243.39 ± 7.19 days, While there was 8.33 percentage twinning noticed in intensive system, the same was observed as 25.00 percentage in semi-intensive system.